Comparative studies of GelMA hydrogels: investigating the effect of different source on mechanical, physical and biological properties - Yilmaz, Hilal; Gursoy, Sevda; Calik, Hilal; Kazancioglu, Yagmur; Yildirim, Ridvan; Cakir, Rabia; Gunduz, Oguzhan; Ahmed, Arsalan; Ustundag, Cem Bulent (IOP Publishing Ltd, 2024)
GelMA hydrogels are prominent in biomedical applications due to their innate extracellular matrix mimicking properties. They exhibit favorable properties for cell proliferation and formation of light-induced hydrophilic cross-linked structures. However, there is limited research on the effect of variations in the starting material (gelatin) on the physical, mechanical and biological properties. In this study, Gelatin Methacrylic Anhydride (GelMA) hydrogels were synthesized from two different products of type B gelatin and loaded with polyvinylpyrrolidone (PVP) nanoparticles by electrospray method. Chemical and structural analyses were performed by FTIR, 1HNMR, TNBS and SEM, respectively. Mechanical properties were evaluated by compression tests. Cytocompatibility was evaluated by XTT analysis. GelMA hydrogels obtained from two brands have suitable pore size, mechanical strength, swelling properties and cytocompatibility, making them suitable for various biomedical applications. In addition, the addition of PVP nanoparticles can make them useful for drug delivery applications.
Keywords: gelatine; GelMA hydrogel; PVP nanoparticle; tissue engineering; GELATIN METHACRYLOYL GELMA; POLYVINYLPYRROLIDONE PVP; CONTROLLED-RELEASE; DRUG-DELIVERY; NANOPARTICLES; DESIGN; Materials Science